Seed dormancy types and germination characteristics of six plants in the dry-warm valley of Jinshajiang River, SW China - Dong, Lijuan; Geng, Boyang; Xu, Yuting; Yu, Wei; Yang, Li-E; Peng, Deli (PeerJ, 2025)
Seed dormancy and the requirements for germination following dormancy release are critical factors influencing the success of seedling establishment. This study examined six plant species from the dry-warm valley region of the Jinshajiang River in southwestern China, investigating their seed dormancy types and germination characteristics. Initially, germination tests were conducted using freshly matured seeds at alternating temperatures of 25/15 and 15/5 °C under light conditions. Subsequently, after dry after-ripening (DAR), germination was retested. Additionally, dried seeds were incubated under a range of constant temperatures (5–37 °C) under light conditions. The effects of darkness and GA3 on seed germination were evaluated at alternating temperatures of 25/15 and 15/5 °C. Cardinal temperatures and thermal time requirements for 50% final germination (θ50) were determined. The increase in final germination following seed coat scarification indicated that Sophora davidii seeds exhibited physical dormancy at dispersal. Treatment with DAR and/or GA3 effectively alleviated dormancy in the other five species (Osteomeles schwerinae, Excoecaria acerifolia, Leonurus japonicus, Incarvillea arguta, Berberis concolor), particularly at the cooler temperature regime of 15/5 °C, suggesting that these species possess non-deep physiological dormancy. Once dormancy is alleviated, seeds of all six plant species can germinate across a broad temperature spectrum, and the temperature window (Tb-Tc) for germination is much wider than the actual germination range. Alternating temperatures did not significantly enhance germination rates compared to constant temperatures, except for L. japonicus. Seeds of L. japonicus exhibited a strict light requirement for germination at alternating temperatures of 25/15 and 15/5 °C, whereas the other five plant species germinated effectively in darkness at the warmer alternating temperature of 25/15 °C. Thus, our hypothesis that dormancy and germination traits restrict germination to the summer (rainy season) is supported. This ensures that seedlings can establish themselves once soil moisture and temperature conditions become favorable. This research offers a valuable scientific reference for vegetation restoration efforts in dry-warm valley regions.
Keywords: Cardinal temperatures; Dry valley; Dry after-ripening; Non-deep physiological dormancy; Light requirement